(untitled) (Eurasian Research Bulletin, 2023)
This article analyzes the emergence of the blogosphere and bloggers themselves on the global Internet, which gave a powerful impetus to the development of the information sector and the expansion of the social reality of modern society. The author has considered in detail the emergence of new methods, technologies and communication channels that are constantly being transformed